Prenatal stress enhances NNK-induced lung tumors in A/J mice - Ito, Tomoaki (Carcinogenesis, 2020)
Children born to women who experience stress during pregnancy have an increased risk of cancer in later life, but no previous animal studies have tested such a link. We questioned whether prenatal stress (PS) in A/J mice affected the development of lung tumors after postnatal response to tobacco-specific nitrosamine, 4-(methylnitrosamino)-1-(3-pyridyl)-1-butanone (NNK). Timed-bred A/J mice were randomly assigned on gestation day 12.5 to PS by restraint for 5 consecutive days or control (no restraint). Adult offspring of control and stressed pregnancies were all treated with three NNK injections (50 mg/kg every other day) and euthanized 16 weeks later to examine their lungs. Compared with controls, PS dams exhibited significantly increased levels of plasma corticosterone, increased adrenal weights and decreased fetus weights without fetal loss. Prenatally stressed litters had a significantly higher neonatal death rate within first week of life, and surviving male and female offspring developed lung epithelial proliferations with increase multiplicity, increased area and aggressive morphology. PS also induced more advanced atypical adenomatous hyperplasia lesions. We found no difference in lung NNK-derived methyl DNA adducts, but PS did significantly enhance CD3+ T cell and Foxp3+ T cell tumor infiltration. PS significantly increases multiplicity, area of NNK-induced lung tumors and advanced morphology. PS did not affect production of NNK-derived methyl DNA adducts but did increase lymphocytic infiltration of lung tumors. To our knowledge, this is the first animal model of PS with evaluation of cancer development in offspring.